Food waste management: The Retail Industry and Consumers’ Contribution in curbing it. - Coetzee, Jan-Louis (The IIE, 2022)
Population increases and global food security issues have prompted a rise in food waste. Even in emerging nations like South Africa, there is an absence of statistics on food wastage. Since South Africa's retail and domestic food waste disposal is a topic of interest, we set out to report our results. The research region includes the metropolitan Pretoria area, which has a population of around 2,74 million, or about 5% of the South African population. A representative sample of the examined communities was gathered by interviewing three participants from previously disadvantaged communities who now reside in urban areas. The retail industry and uninformed customers accounted for the majority of the food waste, and there was particular concern voiced about food loss that could have been used by areas facing food insecurity. The difficulty of educating rural communities about food waste management has been explored and determined to be achievable using social media and other media sources such as radio. The chosen brand, Food Lover's Market, showed to be viable in helping to reduce food insecurity in impacted regions by helping to control food waste and promote themselves as a relevant brand.
Keywords: Retail; Meaningful brands; Social media; Consumer behavior